2006
DOI: 10.1007/s00330-006-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and vertebral artery dissections: clinical aspects, imaging features and endovascular treatment

Abstract: Extracranial arterial dissections are a recognised cause of stroke, particularly in young adults. Clinical diagnosis may be difficult, and the classical triad of symptoms is uncommon. Imaging plays a pivotal role in the diagnosis of extracranial arterial dissections, and this review provides a detailed discussion of the relative merits and limitations of currently available imaging modalities. Conventional arteriography has been the reference standard for demonstrating an intimal flap and double lumen, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 88 publications
2
144
2
Order By: Relevance
“…Risk factors for arterial dissection include connective tissue disorders, hypertension, diabetes mellitus, smoking, hyperlipidemia, oral contraception, and others. 5,17 One study found fibromuscular dysplasia (FMD) in 15% of cases of spontaneous dissection of the carotid or vertebral arteries. 18 Our patient had imaging findings suggestive of FMD, but not associated with either of the vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk factors for arterial dissection include connective tissue disorders, hypertension, diabetes mellitus, smoking, hyperlipidemia, oral contraception, and others. 5,17 One study found fibromuscular dysplasia (FMD) in 15% of cases of spontaneous dissection of the carotid or vertebral arteries. 18 Our patient had imaging findings suggestive of FMD, but not associated with either of the vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia or infarction may occur distal to the territory of the occluded vasculature. 5 A complication of VAD includes ischemia in the vertebro-basilar artery (VBA) distribution, but stroke in young adults secondary to VAD is far less common than those secondary to dissection of the internal carotid artery. 2,19 A literature review that combined carotid and vertebral artery (cervical artery) dissections indicated that a minority of dissections (6%) were associated with SMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Appropriate imaging studies should be performed urgently when a neurological finding is obvious and, more importantly, even if one has only a suspicion based on the mechanism of the traumatic event. 5 In this review, disease was diagnosed in all 34 patients only after the onset of ischemic symptomatology. In patients involved in accidents resulting in polytrauma, routine imaging of the spine is often performed, and based on this evaluation, MR and/or CT dissection protocols should be part of the evaluation.…”
mentioning
confidence: 99%